The adverse selection effect of corporate cash reserve: Evidence from the acquisitions solely financed by stock - Ning Gao (The University of Manchester, Manchester Business School, 2008)
Rhodes-Kropf and Viswanathan (2004) suggest an adverse selection role of corporate cash reserve. Specifically, if investors know a bidder does not have to issue to invest, an attempt to do so sends a strong pessimistic signal of overvaluation. Despite its intuitiveness, this notion has not been explicitly studied in the empirical literature. Using a sample of acquisitions that are solely financed by the bidders' equity to exclude the potential complications of free cash flow, I find that firms with higher excess cash reserve are more likely than other firms to attempt acquisitions that are solely financed by stock. I further confirm that a bidder's excess cash reserve has an adverse wealth effect at deal announcement. The adverse wealth effect of cash reserve is stronger in the hot equity market period when aggregate information asymmetry is arguably high, and for the bidders whose stand alone values are more difficult to assess. In the post-acquisition years, highexcess-cash-reserve bidders operationally out perform low-excess-cash-reserve ones. Moreover, they spend more funds on debt reduction but no more on investments than low-excess-cashreserve bidders do. Combined, these results conform to the adverse selection effect of corporate cash reserve, and suggest that a firm holding more cash than what it requires may incur further costs in addition to the liquidity discount.
Keywords: G34; G32; 330; adverse selection effect of corporate cash reserve; excess cash reserve; overvaluation; two-sided information asymmetry; bidder announcement return; operational cash flow performance; use of funds; Übernahme; Unternehmensfinanzierung; Betriebliche Finanzwirtschaft; Asymmetrische Information; Adverse Selection